Pengaruh Beban Kerja, Disiplin Kerja, Kepuasan Kerja Dan Komitmen Organisasi Terhadap Turnover Intention - Kolompoy, Desko (JURNAL RISET BISNIS DAN MANAJEMEN, 2019)
The resul of this workload significant to turnover intention, discipline work influence not significantly to turnover intention, satisfaction work influence not significant to turnover intention, commitment organizaztional influential not significantly to turnover intention, the influence of workload, discipline work, satisfaction work and commitment organizational simultaneously not significantly to turnover intention. In the future, the management Of PT. Gift Success Commond The Branch of Manado could pay more attention of worloud employees that affect turnover intention. Next need to also noticed a discipline issue work, as well as the commitment organizationKeywords: Workload, Work Discipline, Satisfaction, Turnover Intention